Determination of Optimal Production Number by Considering the Use of Raw Materials Using Goal Programming Approach - Ikhsan Siregar (Universitas Sriwijaya, 2018)
The company produces PVC pipes in Medan city is experiencing problems in the form of a higher number of requests compared to the production number. This is because the company does not have a good production plan which is the results in not meeting consumer demand. For this reason, a good and integrated production planning is needed by using the goal programming method. Production planning carried out with goal programming aims to maximize company profits. The results shows that by using the goal programming method, the optimal production number was obtained at each type of 2-inch ECO JIS D pipe products of 42851 units, 3-inch ECO JIS D pipe products of 54445 units and 4 inches of ECO JIS D pipe products 24480 units. In addition, by using this method the company profits about Rp. 446,620,100 is greater than the actual method applied by the company.